2010
DOI: 10.1177/0022034510385688
|View full text |Cite
|
Sign up to set email alerts
|

Pocket Epithelium in the Pathological Setting for HMGB1 Release

Abstract: High-mobility group box-1 (HMGB1) protein acts as a transcription factor in the nucleus and also as a pro-inflammatory cytokine when released into extracellular fluids. The presence of higher levels of HMGB1 is reported in the gingival crevicular fluid from periodontal patients. Since the proliferation of bacteria within the periodontal pocket is closely involved in the exacerbation of periodontal disease, it is hypothesized that the periodontal pocket causes the release of HMGB1. Immunohistochemical staining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 33 publications
(51 reference statements)
2
29
1
1
Order By: Relevance
“…Consequently, HMGB1 may be located in the cytoplasm of epithelial cells lining the gingival crevice, which harbors mature dental plaque rich in butyrate. This hypothesis is consistent with a report that HMGB1 was present mainly in the cytoplasm of periodontal-pocket gingival epithelial cells (91). In such environments, acetylated HMGB1 in the cytoplasm can be easily released from the gingival cells by butyrate-induced autophagic cell death.…”
Section: Possible Relationship Of Cell Death To Periodontal Diseasesupporting
confidence: 93%
See 1 more Smart Citation
“…Consequently, HMGB1 may be located in the cytoplasm of epithelial cells lining the gingival crevice, which harbors mature dental plaque rich in butyrate. This hypothesis is consistent with a report that HMGB1 was present mainly in the cytoplasm of periodontal-pocket gingival epithelial cells (91). In such environments, acetylated HMGB1 in the cytoplasm can be easily released from the gingival cells by butyrate-induced autophagic cell death.…”
Section: Possible Relationship Of Cell Death To Periodontal Diseasesupporting
confidence: 93%
“…Therefore, destruction of the cell membrane may cause HMGB1 to leak from cells. In fact, Ebe et al reported that butyrate-induced death of Ca9-22 gingival epithelial cells was accompanied by necrotic features, and they concluded that dead cells may release HMGB1 (91). In sum, these studies suggest that autophagic cell death is closely related to butyrate-induced HMGB1 release.…”
Section: Possible Relationship Of Cell Death To Periodontal Diseasementioning
confidence: 91%
“…Many studies have shown that HMGB1 is secreted from many types of cells, including HGF (22), under stressed conditions (2,(8)(9)(10). The gingival crevicular fluid (GCF) of patients with periodontal disease contains high levels of HMGB1 (23), possibly released from inflamed epithelium in periodontal pockets (24), as well as activated immune cells (2,5). Extracellular HMGB1, apart from its cytokine activity, affects the proliferation and/or migration of many cell types (11,12,15,17,25).…”
Section: Discussionmentioning
confidence: 99%
“…A cell monolayer scratch assay is used to evaluate keratinocyte proliferation and migration during re-epithelialization [31]. To assess whether delayed in the wound healing at the wound sites of the Hmgb1 +/− mice is accompanied by retarded re-epithelialization mechanism, gingival epithelial cells were subjected to wound-healing (scratch) assay, in which the ability of cells to migrate and cover the cell-free space is monitored.…”
Section: Resultsmentioning
confidence: 99%